Advanced dynamic IPv6 activation-based defence for IPv6 router advertisement flooding (DoS) attack. (2016) - Goel, Jai Narayan; Mehtre, B.M.
IPv6 router advertisement (RA) flooding is an example of a DoS attack. It leads to denial of service attack on entire local area network. As a result, all systems connected to that LAN get frozen and unresponsive. Hence, it is very important to protect our LANs from IPv6 RA flood attack. In this paper, we describe IPv6 RA flood attack in virtual LAN using KALI Linux. We show its effects on the victim's computer. We propose a new approach to defend from IPv6 RA flooding DoS attack by dynamic IPv6 activation. Such a system would detect the attack and raise a warning alarm. It deactivates IPv6 temporarily. When the host recovers from the attack, the proposed system reactivates IPv6 again. So by using this approach users can use both IPv6 and IPv4 services even under attack. We have also provided pseudo code and experimental results in this paper.